The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/5641185
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Soft and Hard Tissues following Immediate Implant Placement versus Delayed Implant Placement following Socket Preservation in the Maxillary Esthetic Region: A Randomized Controlled Clinical Trial

Abstract: Introduction. Although retrospective analysis has shown immediate placement of implants (IIP) in the maxillary esthetic zone showing promising outcomes compared to delayed placement of implants following socket preservation (DIP), a direct comparison in a prospective, well-designed randomized fashion with adequate power analysis between the two implant placement protocols is still lacking. This study is aimed at radiographically evaluating the effect of IIP after extraction as compared to implant placed in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Socket preservation is a technique defined as alveolar ridge preservation within the bone envelope remaining after tooth extraction with the purpose of reducing bone resorption in order to perform a correct implant-supported prosthesis [ 21 ]. The need of socket preservation immediately after tooth extraction should be determined by the aesthetic, functional and risk-related viewpoint [ 13 , 21 ]: in the case of a treatment plan with implant-supported prosthodontics of the extracted tooth with risk of excessive resorption after tooth extraction and/or aesthetic impact of the tooth, socket preservation is suggested [ 22 ]. Alenazi et al underlined the need for socket preservation after tooth extraction in the case of future implant prosthesis in order to have correct bone volume [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socket preservation is a technique defined as alveolar ridge preservation within the bone envelope remaining after tooth extraction with the purpose of reducing bone resorption in order to perform a correct implant-supported prosthesis [ 21 ]. The need of socket preservation immediately after tooth extraction should be determined by the aesthetic, functional and risk-related viewpoint [ 13 , 21 ]: in the case of a treatment plan with implant-supported prosthodontics of the extracted tooth with risk of excessive resorption after tooth extraction and/or aesthetic impact of the tooth, socket preservation is suggested [ 22 ]. Alenazi et al underlined the need for socket preservation after tooth extraction in the case of future implant prosthesis in order to have correct bone volume [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, even the recent bone regeneration studies do not use the patient's perception or PROMs as a primary outcome but as a secondary one. 29,[38][39][40][41] In the systematic review by Nibali and coworkers, 39,42 where the aim was to compare clinical, radiographic, and patient-reported outcomes when regenerative surgery at teeth was used, it was found that only very few studies reported PROMs and meta-analyses were impossible to perform. Another systematic review by Wittneben et al 42 examined patient-reported outcome measures focusing on the esthetics of implant-supported fixed dental prostheses and found corresponding results.…”
Section: Proms In Other Bone Reg Ener Ati On S Tud Ie Smentioning
confidence: 99%
“…Patient‐reported outcome measures are used more frequently in recent studies compared to previous ones. However, even the recent bone regeneration studies do not use the patient's perception or PROMs as a primary outcome but as a secondary one 29,38–41 . In the systematic review by Nibali and coworkers, 39,42 where the aim was to compare clinical, radiographic, and patient‐reported outcomes when regenerative surgery at teeth was used, it was found that only very few studies reported PROMs and meta‐analyses were impossible to perform.…”
Section: Proms In Other Bone Regeneration Studiesmentioning
confidence: 99%
“…These could be reduced by the use of PRF [ 23 ]. The application in the included studies was performed either with PRF as a sole filling material [ 44 , 45 , 46 , 47 , 48 , 49 ] or PRF in combination with bone graft materials and a collagen plug compared to spontaneous healing of the alveolus [ 49 , 50 , 51 ]. Eight out of 32 articles dealing with this topic were included in our analysis.…”
Section: Main Textmentioning
confidence: 99%
“…For this purpose, studied parameters were defined as dimensions of alveolar bone and its changes [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], new bone formation [ 44 , 46 , 47 , 51 ], pain [ 49 , 50 , 51 ], swelling [ 51 ], soft tissue healing [ 48 , 49 , 51 , 52 , 53 ]. Follow-up for soft tissue healing was documented in the first postsurgical week [ 44 , 45 , 47 , 48 ] and for hard tissue healing between up to 6 months [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Main Textmentioning
confidence: 99%